Diagnostics, Risk Factors, Treatment and Outcomes of Acute Kidney Injury in a New Paradigm - Cheungpasitporn, Wisit; Thongprayoon, Charat; Kaewput, Wisit (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
Acute kidney injury (AKI) is a frequent clinical syndrome among hospitalized patients, independently associated with both short- and long-term mortality. Previous investigations attempted to identify effective interventions to prevent AKI or promote kidney function recovery in patients with AKI. Most were unsuccessful. Hence, additional studies are required in the field of AKI research. In this Special Issue, we are making a call to action to stimulate researchers and clinicians to submit their studies on AKI conducted in nephrology, internal medicine, critical care, and other disciplines that will provide additional knowledge and skills in the field of AKI research, ultimately to improve patient outcomes.